Community-associated methicillin-resistant Staphylococcus aureus infections in Aboriginal children attending hospital emergency departments in a regional area of New South Wales, Australia: a seven-year descriptive study (Western Pacific Surveillance and Response, 2017)
Objective: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) can cause bacterial skin infections that are common problems for Aboriginal children in New South Wales (NSW). MRSA is not notifiable in NSW and surveillance data describing incidence and prevalence are not routinely collected. The study aims to describe the epidemiology of CA-MRSA in Aboriginal children in the Hunter New England Local Health District (HNELHD).Methods: We linked data from Pathology North Laboratory Management System (AUSLAB) and the HNELHD patient administration system from 33 hospital emergency departments. Data from 2008–2014 for CA-MRSA isolates were extracted. Demographic characteristics included age, gender, Aboriginality, rurality and seasonality.Results: Of the 1222 individuals in this study, 408 (33.4%) were Aboriginal people. Aboriginal people were younger with 45.8% aged less than 10 years compared to 25.9% of non-Aboriginal people. Most isolates came from Aboriginal people who attended the regional Tamworth Hospital (193/511 isolates from 149 people). A larger proportion of Aboriginal people, compared to non-Aboriginal people, resided in outer regional (64.9% vs 37.2%) or remote/very remote areas (2.5% vs 0.5%). Most infections occurred in summer and early autumn. For Aboriginal patients, there was a downward trend through autumn, continuing through winter and spring.Discussion: Aboriginal people at HNELHD emergency departments appear to represent a greater proportion of people with skin infections with CA-MRSA than non-Aboriginal people. CA-MRSA is not notifiable in NSW; however, pathology and hospital data are available and can provide valuable indicative data to health districts for planning and policy development.